AN ASSESSMENT OF THE AESTHETIC VALUE OF THE ISLAMIC UNIVERSITY MOSQUE IN CONSTANTINE - Said, Bousmaha; Chergui, Samia; Zouaoui, Mustapha Cheikh (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2019)
Contemporary architecture increasingly stands out as a new area of cultural heritage. The